The reality of strategic renewal in enhancing the strategic sovereignty of the managers of sport federations - Ghali Mahawi, Hasan (International Journal of Psychosocial Rehabilitation, 2023)
The study aimed to identify the relationship between strategic renewal and the promotion of the strategic sovereignty of the heads of sports federations. Business, opportunities, as for the measure of strategic sovereignty and its dimensions, competitive pressure, sphere of influence, and competitive formation. And he identified the research problem by studying the reality of strategic renewal, and the ingredients And the capabilities of sports federations to contribute to achieving strategic sovereignty in light of sports competition and entry into the era of globalization and the establishment of profit-making institutions as well as sports investment, as a sample was deliberately chosen from the heads and members of sports federations, numbering 118, and the researcher used the spss statistical bag to interpret the results and found a relationship Significant correlation between search variables .